Predicting the Effect of Work-FamilyConflict on Job Satisfaction among General Practitioners - Khizar, Dr. Umbreen; Khalid, Ramesha; Nawaz, Dawood; Baloch, Umber (The journal of contemporary issues in business and government, 2021)
The aim of this research was to predict the effects of work-family conflict on job satisfaction among Pakistani general practitioners. The study consisted of 184 general practitioners from different units of Nishtar Hospital Multan and Fatima Jinnah Women Hospital Multan. The 10items work-family and family-work conflict questionnaire was used to assess work-family conflict and the instruments were taken from the study conducted by the Boyar and Carson (2006). However,the 20 items Minnesota Satisfaction Questionnaire created by Weiss and Dawis (1967) was used to assess an individual’s level of job satisfaction for this study.Using regression analysis, there wasevaluated that work-family conflict has a significant effect on job satisfaction among the general practitioner. Further, there were no major differences in the degree of work-family conflict and job satisfaction among general practitioners based on gender or marital status according to independent samples t-test. Using ANOVA, significant variations in the degree of work-family conflict in general practitioners were analyzed based on their age. However, there was no significant variance in work satisfaction levels based on age. In the future, it will be fascinating to see how disparities in marital status and gender affect general practitioners.